Impact of The Number of Light Emitting Diode Towards The Accuracy in Indoor Positioning System Based on Visible Light Communication - Brian Pamukti; Miftakhul Meiliana Rahmawati; Nachwan Mufti Adriansyah (National Research and Innovation Agency, 2020)
This research detects the random position with received signal strength (RSS) method based on the received power in the room with a size of 5×5×3 cubic meter and several numbers of light emitting diode (LEDs). The first scenario uses 4 LEDs, the second scenario uses 6 LEDs and the third scenario uses 8 LEDs. Random points as the detector are placed spread at the room as many as 25 points. The simulation result shows that the use of more LEDs reduces the positioning error and increases the accuracy. If the accuracy reduces, the positioning error increase and affect the detection results. Using 8 LEDs, the number of the detected random point increases 30%, the positioning error is 47%, and the accuracy increase from 33%. In addition, our research is useful for finding the locations of small items such as sensors that are scattered in a closed room.